Listening to Rural Adolescents: Views on the Rural Community and the Importance of Adult Interactions - Dalva Hedlund (Journal of Research in Rural Education, 1993)
The problems facing rural areas are many faceted, but a key component to their solution is the human resource of ruraladolescents. In this study, an interpretiveanalysisofinterviews focusingon perceptions of the community, family, school social dynamics, and aspects of self identity with 20 adolescents from a rural high school, is discussed within the framework of two organizing dimensions: living in a rural community and the importance of adult-adolescent interactions. Participants both liked and disliked growing up in a small rural community. The interpersonal intimacy of a rural community was seen as providing a sense of safety and belonging while taking away personal privacy and fostering prejudices. Perceptions of community isolation include lack of social activities, difficulty with transportation, and, positively, an identification with nature. Adult interactions that were perceived as important range from global perceptions of community support for school and adolescent activities to interpersonal contacts with teachers, family members, and other adults. Participants seemed tobesimply asking to beheard and responded toas individuals. The importance oflistening and understanding the unique concerns of adolescents in each rural community is emphasized. Schools and communities need to work together locally to support the plans that most rural young people would seem to naturally make: to live in a rural area to work and raise their own families.